ANALISIS FAKTOR ATAS NON-PERFORMING FINANCING BPR SYARIAH DI INDONESIA PERIODE 2012-2014 - Endah Sulastri; Sugeng Hariadi; Mintarti Ariani (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2016)
The purpose of this research is to analyze the influence the Non Performing Financing in Sharia Rural Banking in Indonesia (BPRS). As some of the factors analyzed in influence of Non-Performing Financing (NPF) is Gross Domestic Product (GDP), Exchange Rates, policy type of financing Islamic banks as well as the allocation ratio murabaha receivables rather than the allocation of profit loss sharing financing (RF). The population in this study was all Sharia Rural Banking in Indonesia (BPRS). Data used was time series data with quantitative approach and analyzed using OLS (Ordinary Least Square). The result of this research indicate that the growth of GDP had a negative impact on the Non Performing Financing (NPF) and significant; exchange rate had a negative impact on the Non Performing Financing (NPF) but not significant; profit and loss sharing ratio of return on total return of financing (RR) has a significant negative effect on the Non Performing Financing (NPF). Murabaha financing allocation ratio to the allocation of profit loss sharing financing and a significant negative Effect on Non Performing Financing (NPF).